GENETIC VARIABILITY OF IRANIAN ADANI GOAT BREED USING PEDIGREE ANALYSIS - S. Joezy-Shekalgorabi; A. Maghsoudi; A. Taheri-Yeganeh; B. Rajabi-Marand (Journal of Animal and Plant Sciences, 2017)
In the current research, genetic diversity of Iranian Adani dairy goat was assessed utilizing pedigree analysis. Pedigree records from a total of 2985 animals during 1999-2013 were analysed. A total of 96 animals were inbred. The average inbreeding coefficients in the whole, the inbred and the reference population (living reproductive animals born from 2009 to 2013) were found 0.24, 7.33 and 0.56 %, respectively. The low inbreeding coefficient obtained forAdani dairy goat was mainly related to the lack of sire registration in a large number of animals (about 44.4% missing sire information). Low ratio of the effective number of founders (fe) to the total number of founders (f) (fe/f=0.13) for Adani goat breed represents unbalanced contribution of founders to the reference population. Effective number of ancestors (fa) was equal to 39. The Ratio of fe to fa was1.44 which could be a result of occurring genetic bottleneck in the population and the use of a limited number of parents across generations. Low equivalent generation obtained for the Adani dairy goat indicates low pedigree depth in the studied breed and the need for using molecular based methods to overcome the problem of pedigree incompleteness in this breed.
Keywords: Adani dairy goat; Inbreeding; Iran; Pedigree analysis